Historical Values and Character Education Based on Batu Urip Local Wisdom as a History Learning Resource - Susilo, Agus; Satinem, Yohana; Sarkowi, Sarkowi (Universitas Negeri Padang, 2025)
The declining interest of the younger generation in history lessons in the digital era is a serious challenge to preserving national identity and forming national character. Many students find history boring and irrelevant. To answer this challenge, an innovative approach based on local wisdom that is contextual and meaningful is needed. The Batu Urip site in Lubuklinggau, which has been designated as a Cultural Heritage Village, holds potential historical and character values that can be integrated into history learning. This research explores the values of history and character education from Batu Urip's local wisdom as a 21st-century learning resource. The method used is historical research, which includes heuristics (data collection through field observations, interviews with traditional leaders, and archival studies), source criticism, interpretation of character values, and historiography writing. The results show that the Batu Urip site contains values such as gotong royong, social responsibility, and love for the environment, which are reflected in artefacts and oral traditions of the local community. The novelty of this study lies in developing interactive digital history learning media based on local values. The study's conclusion confirms that integrating local wisdom in history learning effectively fosters cultural identity, positive character, and students' interest in globalization.